PENGARUH STRATEGI PEMBELAJARAN DAN KEMAMPUAN MATEMATIKA TERHADAP HASIL BELAJAR AKUNTANSI - Restu Wibawa (Universitas Pendidikan Mandalika, 2015)
This study aims to determine the effect of learning strategies and math skills on student accounting learning outcomes. This study used an experimental method with a 2x2 treatment by level design. The data analysis technique used descriptive and inferential statistics with hypothesis testing through two-way ANOVA analysis. The results showed: (1) The group of students who followed the inquiry learning strategy was higher than the group of students who took the CTL learning strategy. (2) There is an interaction between learning strategies and mathematical skills on accounting learning outcomes. (3) The accounting learning outcomes of students who have high math abilities who follow the inquiry learning strategy are higher than the CTL learning strategy. (4) The accounting learning outcomes of the group of students with low math abilities who took the inquiry learning strategy were lower than those who took the CTL learning strategy.